Loss of Olfactory Function—Early Indicator for Covid-19, Other Viral Infections and Neurodegenerative Disorders - Heike Rebholz; Heike Rebholz; Heike Rebholz; Ralf J. Braun; Dennis Ladage; Dennis Ladage; Wolfgang Knoll; Christoph Kleber; Christoph Kleber; Achim W. Hassel (Frontiers in Neurology, 2020)
The loss of the senses of smell (anosmia) and taste (ageusia) are rather common disorders, affecting up to 20% of the adult population. Yet, this condition has not received the attention it deserves, most probably because per se such a disorder is not life threatening. However, loss of olfactory function significantly reduces the quality of life of the affected patients, leading to dislike in food and insufficient, exaggerated or unbalanced food intake, unintentional exposure to toxins such as household gas, social isolation, depression, and an overall insecurity. Not only is olfactory dysfunction rather prevalent in the healthy population, it is, in many instances, also a correlate or an early indicator of a panoply of diseases. Importantly, olfactory dysfunction is linked to the two most prominent neurodegenerative disorders, Parkinson's disease and Alzheimer's disease. Anosmia and hyposmia (reduced sense of smell) affect a majority of patients years before the onset of cognitive or motor symptoms, establishing olfactory dysfunction as early biomarker that can enable earlier diagnosis and preventative treatments. In the current health crisis caused by SARS-CoV2, anosmia and dysgeusia as early-onset symptoms in virus-positive patients may prove to be highly relevant and crucial for pre-symptomatic Covid-19 detection from a public health perspective, preceding by days the more classical respiratory tract symptoms such as cough, tightness of the chest or fever. Thus, the olfactory system seems to be at the frontline of pathologic assault, be it through pathogens or insults that can lead to or at least associate with neurodegeneration. The aim of this review is to assemble current knowledge from different medical fields that all share a common denominator, olfactory/gustatory dysfunction, and to distill overarching etiologies and disease progression mechanisms.